Phonographic Means in Children's Poetry - Shodiyevna, Ashurova Zulkhumor (European Journal of Life Safety and Stability (2660-9630), 2022)
The article deals with phonographic means, special questions of linguopragmatics, poetic speech, poetic text, questions of linguopoetics.